Cherenkov-Type Generation and Detection of Terahertz Radiation in a GaAs With Metal-Coat Structure - Delos Santos, Ramon M (Archīum Ateneo, 2016)
This work demonstrates Cherenkov-type generation and detection of terahertz (THz) waves in GaAs at 1.55-μm excitation and optical sampling probe, respectively. Results show that GaAs with metal-coat (M-G-M) has better performance than a bare GaAs (BG), both as an emitter and a detector because of improved confinement and lower loss of THz waves propagating in M-G-M compared with BG.